Strategi Pengembangan Literasi Digital Santri Melalui Pers Mahrusy di Pondok Pesantren Lirboyo - Beti Malia Rahma Hidayati; Annisa Miftahurrohmah (Jurnal Kopis: Kajian Penelitian dan Pemikiran Komunikasi Penyiaran Islam, 2023)
Technology that is increasingly advanced, and continues to develop, make it possible to support and facilitate the wider internet network and media convergence. This certainly makes it easy for users to get information. Even the educational process has also morphed to adjust to developments in the learning process through various online/online media. This study aims to determine the strategy for developing students' digital literacy through the Mahrusy Press at the Lirboyo Islamic Boarding School HM Al Mahrusiyah. This is important, considering that students are often seen as traditional in modernity. This qualitative research method uses in-depth interview techniques in collecting data. The key informant is the General Manager of the Mahrusy Press with secondary data obtained from observation and documentation techniques. As a result, it is known that the strategy for developing student literacy used by Press Mahrusy so that it becomes one of the reference media for East Java is the holding of The Rules guidebook, giving affirmations on the importance of digital literacy, reading habits, holding Journalistic Korans, conducting literacy studies as a form of follow-up to journalism recitation, following contests or contests that hone the abilities of members, hold comparative studies, and always ask for guidance from active advisors to the Mahrusy Press. It is hoped that future researchers can dig deeper regarding each literacy development strategy or examine it with a different theory.